2005
DOI: 10.1111/j.1365-2265.2005.02339.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone on body composition, bone metabolism and serum lipid profile in middle‐aged men: a meta‐analysis

Abstract: The present analysis provides an estimate of the average treatment effects of testosterone therapy in middle-aged men. Our findings are sufficiently strong to justify further interventional studies focused on alternative targets of androgenic treatment carrying more stringent clinical implications, in particular the cardiovascular, metabolic and neurological systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
476
9
21

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 611 publications
(539 citation statements)
references
References 72 publications
(230 reference statements)
28
476
9
21
Order By: Relevance
“…The reduction in HDL levels may be explained by a reported testosteroneinduced decrease in lipoprotein lipase activity in humans (Rebuffe-Scrive et al 1991), but the mechanism underlying testosterone-induced decrease in HDL levels has not been clarified. Our data were consistent with a meta-analysis (Whitsel et al 2001) and a recent systematic review (Fernandez-Balsells et al 2010) that reported a significant small decrease in HDL cholesterol levels in men treated with testosterone; however, a meta-analysis found no change in HDL cholesterol levels in response to testosterone treatment (Isidori et al 2005). A low HDL is linked to an increased morbidity and mortality of cardiovascular disease, and in a recent study on old men with limitations in mobility, cardiovascular and respiratory events were significantly increased during testosterone therapy compared to placebo (Basaria et al 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The reduction in HDL levels may be explained by a reported testosteroneinduced decrease in lipoprotein lipase activity in humans (Rebuffe-Scrive et al 1991), but the mechanism underlying testosterone-induced decrease in HDL levels has not been clarified. Our data were consistent with a meta-analysis (Whitsel et al 2001) and a recent systematic review (Fernandez-Balsells et al 2010) that reported a significant small decrease in HDL cholesterol levels in men treated with testosterone; however, a meta-analysis found no change in HDL cholesterol levels in response to testosterone treatment (Isidori et al 2005). A low HDL is linked to an increased morbidity and mortality of cardiovascular disease, and in a recent study on old men with limitations in mobility, cardiovascular and respiratory events were significantly increased during testosterone therapy compared to placebo (Basaria et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The increase in LBM was not associated with the testosterone level at inclusion. The changes in body composition were in accordance with the results previously described during testosterone therapy (Isidori et al 2005) also in aging males (EmmelotVonk et al 2008). Skeletal muscle accounts for approximately 80% of the glucose uptake in the insulin-stimulated state (Shulman et al 1990).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Isidori et al (2005)) in another metaanalysis study reported beneficial effects enough to justify the demand for other interventional studies on this issue. On the other hand, there is the existent, but small risk of side effects, showed in another metaanalysis (Calof et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…63 Overviews of randomized controlled trials of testosterone therapy in men without or with underlying chronic illness using a variety of testosterone formulations report improvements in body composition with increased lean body mass and reduced fat mass, but limited benefit in physical capabilities and equivocal improvements in quality of life measures, including general well-being and fatigue. [64][65][66] However, the studies reported tend to be of limited size and duration, with a lack of large-scale trials with extended long-term follow-up. Thus, additional studies have been recommended incorporating vitality, well-being and/or quality of life as end points.…”
Section: Testosterone General Health and Quality Of Life In Aging Menmentioning
confidence: 99%